Improving Communication Accessibility to Public Safety Center 119 Through Integrated Simulation - Sunarto, Sunarto; Harnanto, Addi Mardi; Sudiro , Sudiro (CV. Publikasi Indonesia, 2025)
Emergencies caused by disasters, accidents, and diseases carry risks ranging from disability to death. Rapid emergency assistance is essential to mitigate these risks, with first responders playing a vital role. The Public Safety Center (PSC) 119 serves as a key access point for emergency response, yet public awareness and understanding of how to access it remain limited, particularly among heterogeneous communities. Integrated simulation has emerged as a promising strategy to improve communication accessibility to emergency services. This research aims to analyze the improvement of communication accessibility to Public Safety Center 119 through integrated simulation. The research employed an experimental design with a pretest-posttest model. A total of 217 participants from the general public in Surakarta City, including members of the Volunteer Corps, health cadres, and neighborhood security (Linmas), were involved. Data were collected using questionnaires and analyzed via t-test. Statistical analysis revealed a significant increase in communication accessibility scores following the integrated simulation, with a Sig. (2-tailed) value of 0.00. The mean pretest score of 73.5 (medium category) rose to 77.9 (high category) in the posttest, reflecting an improvement of 4.4 points. Integrated simulation effectively enhances communication accessibility to Public Safety Center 119. It is recommended as a practical and impactful approach to raise public awareness, improve emergency access, and strengthen community preparedness in emergency response systems.